Influence of product innovation and influencer marketing on the interest in buying Bluebutton fashion products - Claudio, Randy Arvin; Tarmidi, Didi (Technium Sustainability, 2021)
Analysis to examine thanks to describe product innovation, influencer selling, and buying interests, additionally on confirm but the influence product innovation and influencer selling on the interest in shopping for fashion merchandise in Bluebutton. The factors tested inside the study were product innovation and influencer marketing as freelance variables, whereas buying interests were dependent variables. The analysis methods. employed in this research are descriptive and verification methods. The analysis ways used in.this research.are descriptive and verification methods. The population throughout this study was the one who knew bluebutton fashion products. The sampling technique used within the study was nonprobability sampling and additionally the scale of the sample within the study was calculated by Bernoulli’ formula, that the whole vary was one hundred respondents. The analytical ways employed in this study are some regression analyses victimization SPSS25 Windows. The results this study show that product innovation and influencer marketing have an impression on the interest in buying Bluebutton fashion products. The magnitude of the influence of product innovation.and influencer marketing on buying interest by 40.4%.